Parents' Leadership Patterns in Motivating the Implementation of Islamic Religious Education in Children - Nisa Cahyani Br Sinuraya; Miswar Rasyid Rangkuti (Universitas Muhammadiyah Enrekang, 2024)
Children's behaviour and morals are greatly influenced by the role of parents in encouraging them to learn about Islam; they will understand the boundaries of what is meant by good and bad deeds if they become human beings devoted to Allah SWT. As parents, children's education is the main thing, especially in Islamic religious education. This research raises several problems, one of which is how parents encourage their children to learn about Islam. This research aims to find out how parents can encourage their children to learn about Islam. This research uses a qualitative descriptive approach that collects data through observation, interviews, and documentation. Research findings show that parents are responsible for guiding, teaching, and inspiring their children by encouraging them to participate in recitations, modelling good behaviour, and providing quality instruction. Children inspired to learn Islam from their parents receive three benefits: becoming more enthusiastic, having strong morals, and being filial to their parents. One of the supporting factors is television.